2021
DOI: 10.1155/2021/5512391
|View full text |Cite
|
Sign up to set email alerts
|

circSLC6A6 Sponges miR-497-5p to Promote Endometrial Cancer Progression via the PI4KB/Hedgehog Axis

Abstract: Background. As a new kind of noncoding RNAs, circular RNAs (circRNAs) have been substantiated to be involved in multiple biological processes. Accumulating studies indicate that circular RNAs (circRNAs) regulate the development of cancers by acting as miRNA sponges. However, the role of circRNAs in endometrial cancer (EC) is rarely reported. This study was aimed at investigating the functional roles of circSLC6A6 in EC. Methods. The qRT-PCR assay was performed to detect the circSLC6A6 expression in EC tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In our study, bioinformatics online tools predicted that LINC00473 might bind to miR-497-5p. Previous studies reported that miR-497-5p was a crucial regulator in inhibiting tumorigenesis, and the aberrant expression of miR-497-5p took part in tumor initiation, cancer cell growth, apoptosis, and invasion [29][30][31][32]. More importantly, miR-497 was verified to be increased in the mouse brain after cerebral ischemia, and inhibition of miR-497 could attenuate ischemic cerebral infarction [33].…”
Section: Discussionmentioning
confidence: 96%
“…In our study, bioinformatics online tools predicted that LINC00473 might bind to miR-497-5p. Previous studies reported that miR-497-5p was a crucial regulator in inhibiting tumorigenesis, and the aberrant expression of miR-497-5p took part in tumor initiation, cancer cell growth, apoptosis, and invasion [29][30][31][32]. More importantly, miR-497 was verified to be increased in the mouse brain after cerebral ischemia, and inhibition of miR-497 could attenuate ischemic cerebral infarction [33].…”
Section: Discussionmentioning
confidence: 96%
“…miR-497-5p participates in EC progression and could regulate the phosphatidylinositol 4-kinase beta (PI4KB)/hedgehog signaling pathway. In EC, miR-497-5p mimics decreased the expression of PI4KB and hedgehog in HEC-1B cells (p < 0.01), while miR-497-5p inhibitors increased PI4KB and hedgehog expression in HEC-1A cells (p < 0.01) [78]. miR-497-5p transcriptional targets have been identified in other tumor types.…”
Section: Mirs and Ec Prognosismentioning
confidence: 91%
“…circRNAs are stable and specifically expressed both intracellularly and in extracellular fluid (27). Although circRNAs are generally expressed at low levels (27), increasing evidence has demonstrated that circRNAs are involved in EC (28)(29)(30). circRNAs carry multiple microRNA (miRNA/miR) binding sites, and regulate the activity of target miRNAs through their competitive binding, thereby inhibiting the transcription of downstream products (31).…”
Section: Formation and Classification Of Circrnasmentioning
confidence: 99%
“…circRNAs are closely involved in the regulation of cell proliferation via multiple pathways. At present, several studies have demonstrated that circRNAs adsorb miRNAs through numerous pathways and fulfill a role in EC development (28,29,71). For example, circIFT80 [circBase ID (http://www.circbase.org/), hsa_circ_0067835], circWHSC1, circSLC6A6, circATP2C1 (circBase ID, hsa_circ_0005797) and circPOLA2 participate in the invasion, proliferation and metastasis of EC through the adsorption of miR-324-5p (71), miR-646 (28), miR-497-5p (29), miR-298 (30) and miR-31 (70), respectively.…”
Section: Circrnas Regulate Cell Proliferation and Motility In Ecmentioning
confidence: 99%